Review on Basic Concept for Ophthalmic Preparations - Verma, Priyanka; Verma, Anamika; Namdev, Abhishek; Soni, S. L (Asian Journal of Pharmaceutical Research and Development, 2015)
Ocular drug delivery has been a major challenge to pharmacologists and drug delivery scientists due to its unique anatomy and physiology. Ophthalmic preparations are sterile liquid, semi-solid, or solid preparations intended for application to the conjunctiva, the conjunctival sac, or the eyelids. Sterility is very important factor in manufacture and use of ophthalmic products. Preservative selection is also an important activity in product design. Other important aspects requiring assessment in the manufacture of ophthalmic products include sterility, tonicity, pH, buffering, drug toxicity, solubility, stability, viscosity, aseptic filling, packaging and storage. Microbial content, in-process intermediates, and drug substance or active product ingredient are potential sources of contamination and require incoming testing of ingredients. The current developments in this field of ophthalmic drug delivery promise a significant improvement in overcoming the challenges posed by various anterior and posterior segment diseases.